Effective Use of Media About Sex Education on Adolescent Attitudes in Preventing Unwanted Pregnancy - Sri Hazanah (International Journal Labs, 2022)
Sexual behavior begins to function during the reproductive period starting in early adolescents aged 12-15 years. If sexual behavior is not addressed immediately, the increase in unwanted pregnancies among young adolescents will be a cause for concern and information on sex education should be provided both at home and at school. The research analyzed the effective use of media about sex education on adolescent attitudes in preventing unwanted pregnancy in Balikpapan. The research method was survey and cross sectional with 181 samples of early adolescents aged 12-15 years, the sampling technique used Random sampling. Univariate analysis was carried out by descriptive analysis to see the characteristics of each variable studied, bivariate analysis was performed using the Chi Square test (x2), (p value <0.25). The results of the research on adolescent attitudes before the intervention of 181 respondents, 89 respondents (.49.2%) were good, as many as 83 respondents (45.9%) were moderate and 9 respondents (5.0%) were not good. Adolescent attitudes after intervention from 181 respondents, 95 respondents (52.5%) were good, as many as 86 respondents (47.5%) were moderate. After conducting the marginal homogeneity test, it shows a p value of 0.002 which means> 0.05, there is a relationship between the provision of sex education using media to changes in teenagers attitudes.